MAKNA MAKANAN TRADISIONAL TUMPENG SEBAGAI SUMBER PEMBELAJARAN IPAS BERBASIS KEARIFAN LOKAL DI SEKOLAH DASAR - FAIQOTUL HIMMAH FAIQOTUL (Jurnal Primary (Kajian Ilmu Pendidikan Dasar dan Humaniora), 2022)
This study aims to describe Tumpeng as a traditional food, both history and various features in the dish, as well as the meaning contained in Tumpeng which is one of Sidoarjo's local wisdom. The research method used by researchers in this study is a qualitative approach with descriptive methods. Tumpeng is interpreted as an illustration of the human relationship with God, the relationship with fellow human beings and the relationship with the universe. Tumpeng means that humans live life with enthusiasm and walk the straight path, even since they were born. Tumpeng depicts the human relationship with God, human nature and the universe that was created by God and will return to Him and human hope for God so that they are always given safety, a good life and achieve inner perfection. Tumpeng contains learning for humans how to live life, namely maintaining human relationships with God, relationships with fellow human beings, and with the universe. Tumpeng, besides being good in shape and taste, also has a deep meaning for humans.